Outline of an intellectual biography of Professor Waldemar Dutkiewicz (1939–2007) - Paweł Grzybek (Studia Medyczne, 2017)
The date of February 19, 2017 has marked the 10th death anniversary of Prof. Waldemar Dutkiewicz, who was an outstanding pedagogue, organiser of didactic and educational work, great social worker, and above all an eminent scholar. Professor Dutkiewicz died suddenly on February 19, 2007, still with his full creative forces. The professor was born on June 2, 1939 in Rivne, in Volhynia. In the period 1957–1963 he studied at the School of Physical Education in Krakow. He completed his pedagogical studies in 1970 at the Higher School of Pedagogy in Krakow. In 1973 he obtained a doctoral degree in physical education. His doctorate in pedagogy was publicly defended in 1982. At the Academy of Physical Education in Warsaw he received his Doctor of Letters (habilitation) degree in the field of physical education in 1986. By a decision of the President of the Republic of Poland of August 22, 1995 he was awarded the title of Professor. Due to his studies and didactic work the heritage of Professor Dutkiewicz is composed of two parts: auxological and pedagogical.